The Effectiveness of Using Educandy in ELT to Improve Students’ Vocabulary Mastery - Khoirunnisa Khoirunnisa; Muh Shofiyuddin; Olyvia Revalita Candraloka (Darussalam English Journal (DEJ), 2023)
This study aimed to find out the Effectiveness of using Educandy in improving English vocabulary mastery of seventh grade students at MTs. Safinatul Huda 02 Karimunjawa. This emphasized on reinforce students vocabulary in learning process. This study used an Experimental method, with a treatments. The data was obtained by means of multiple choice and Essay questions. Evidenced by obtaining a Normality test with a sig. 0.200 is greater than 0.05 which means the research data is normally distributed. The results of calculation using SPSS 23. In the equal variances assumed section, the value of sig. 2-tailed was 0.000 < 0.05. this shows that there is a significant difference in the mean scores of students in the experimental class and the control class. Therefore, H0 is rejected and Ha is accepted. Then the t-observe is higher than the t table, which is 8.025 > 2.000 with a significance level of 5%. Based on the analysis of the results, the researcher concluded that the use of Educandy can improve students vocabulary mastery.